CADMIUM TOLERANCE AND RESISTANCE TO DAMAGE BY Bemisia tabaci INDUCED BY A CONSORTIUM OF ARBUSCULAR MYCORRHIZAL FUNGI IN Solanum lycopersicum L. - Shirley Margarita Amaya-Martin; Horacio Salomon Ballina-Gomez; Carlos Juan Alvarado-López; Esau Ruiz-Sánchez; Maria Lourdes Gil-Cardeza; Gabriel De Jesus Azcorra-Perera (Tropical and Subtropical Agroecosystems)
Background. Cadmium (Cd) is a potentially toxic element that when released in permeable soils such as those of Yucatan enters directly into the horticultural systems and in general into the food web causing several problems. It is known that tomato (Solanum lycopersicum L.) shows tolerance to the element cadmium and resistance to damage by various pests, however, the biological mechanism that is triggered in its interaction with microorganisms under this type of stress conditions is little known. Objective. To analyze the effect of a consortium of arbuscular mycorrhizal fungi on Cd tolerance and resistance to B. tabaci damage in S. lycopersicum L. Methodology. A split-plot design was used with the following factors: 1) mycorrhizal fungal consortium: control (M–) and mycorrhizal fungal (M+); 2) damage by B. tabaci: control (D-) and presence (D+); and 3) addition of Cd at three levels: control (C), Cd at 0.005 ppm (Cd+) and Cd at 0.020 ppm (Cd++). Mycorrhization, growth and plant defense were estimated. Results. Colonization of 39% and 49% was found, even with the addition of Cd+ and Cd++, respectively. Likewise, positive effects of mycorrhizal fungi on plant height growth and leaf thickness were recorded, interestingly despite the addition of cadmium. Also, compensatory growth responses in terms of leaflet production were recorded, but in the absence of mycorrhizal fungi and in the presence of B. tabaci. Additionally, the mycorrhizal fungi produced less hard leaves in the presence of B. tabaci, which suggests an effect of an improvement in the nutritional quality of the leaves. Implications. Plant growth of tomato plants could be as result of inherent plant growth more than other extrinsically factors such as cadmium or B. tabaci. Conclusions. Tomato plants showed positive effects on cadmium tolerance and resistance to damage by B. tabaci, although inherent plant growth could be a very important mechanism to be considered in the future.